Budaya Peduli Arsip dalam Pengelolaan Arsip Digital Berbasis Web: Studi Kasus pada Kantor Lembaga Layanan Pendidikan Tinggi Wilayah VI Jawa Tengah - Sumarno Sumarno; Titiek Suliyati (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Creating A Culture Of Archives Care Through WebBased Digital Archives Management. This article is the result of research on web-based digital archive management, which was conducted at the Higher Education Service Institute (LLDIKTI) Region VI Central Java. In the digital era, such as when technology is indispensable in managing archives. Records management with the support of information technology can be carried out quickly and efficiently. Success in digital archive management will solve the problem of space limitations. This research was conducted using a descriptive qualitative method that is very appropriate to solve the problems studied, especially to examine case studies. The problem to be studied is how the management of web-based digital archives in LLDIKTI Region VI Central Java is carried out efficiently. Data collection is done by observation, in-depth interviews, literature studies and documents. Data analysis was carried out with the stages of data reduction, data presentation and data verification or conclusions. The results show that web-based digital archive management in LLDIKTI Region VI Central Java still needs to be developed, especially in the Archives Unit, which is the center for archiving services. For maximum results in web-based digital archive management, it requires the commitment of the leadership and all available resources so that archive management can be carried out effectively and efficiently.